Hatten Hotel (Melaka) Sdn Bhd / Sarah Nabila Azril Fauzi - Azril Fauzi, Sarah Nabila (Faculty of Business and Management, 2023)
First and foremost, the internship that I have been waiting for is finally here where I have successfully gained my position in the financial department of a 5-Star hotel in Melaka, famously known as Hatten Hotel. According to my previous used resume that I have also used for my internship application, it includes many areas namely my education backgrounds and awards since high school up until universities specifically for diploma and bachelor, languages that I have learnt or fluent in speaking, as well as my precious first working experience as a cashier in 2021. I also took the time to present my basic skills that I have learnt throughout my studies like teamwork skills and technical skills such as the ability to use Adobe and Microsoft Office. It would be a loss if I don't mention about my contact number and official emails in my resume because it would be helpful if the organization is interested to take me into their organization. Other than my student profile, I also mentioned some of the company’s profile in the next part of the report. First point is about its strategic location at the center of Malacca city surrounded by popular shopping malls and Malacca’s historical landmarks suitable for travelers to explore Melaka and its unique authenticity. After that, next point is about the company’s vision and mission that aims at giving absolute hospitality experiences to its local and international guests which can be concluded as customer-oriented goals. Next is the background of establishment that mentions about the chairman of Hatten Group of Companies, Y. Bhg. Datuk Wira Eric Tan Eng Huat. There also two organizational structure included in the report which are for HHW and Hatten Hotel Melaka. Aside from mentioning about Hatten’s various kinds of suite accumulating to a total of 700 rooms, the report also include other facilities like pool and restaurants as well as Estadia Hotel’s Baba Nyonya culture style of suites. After that, it focuses on the topic of student's training reflection that is further divided into four parts which are duration, department, duties and responsibilities as well as the benefits of being an intern at Hatten Hotel. Finally, the report has come to its main part which is about the SWOT of the company specifically for its finance department. The strengths of finance department is related to its skillful staff and strong financial performance, while the department is weak in terms of manpower shortage during seasonal increase and the activity of unnecessary printing. In order to enhance these strengths, company trip and team building are a promising effort, while business digitization will help to improve its weakness. The department can enhance their opportunity of having digital financial system and professional IT by technology training all department staff. Lastly, it is vital for the company to adopt rewards system that can stop the threat of staffs unethical behavior such as theft.